PENGARUH BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN MOTOR SCUTER MATIC YAMAHA DI KOTA AMBON - Paseru, Janto (Fakultas Ekonomi Universitas Wisnuwardhana, 2015)
This study aims to determine and measure whether the variableswhich include corporateimage brand image, user image and productimage simultaneously influence the purchasing decisions scuter maticYamaha motorcycle, and to determine which variables are the dominantinfluence on purchase decisions scuter matic Yamaha motorcycle.Theresearch data was collected through questionaire distributed to 100 usersscuter matic Yamaha motorcycle in the city of Ambon. Collected data isprocessed using SPSS 21 and analyzed using multiple regressionanalysis.These results indicate that all variables brand image whichconsists of corporate image (X1), the user image (X2) and product image(X3) simultaneously and partially on purchasing decisions scuter maticYamaha motorcycle in the city of Ambon. While the variable productimage (X3) is the most dominant variable in influencing consumerpurchasing decisions.Keywords: brand image, corporate image, user image, product image,purchasing decisions